The British Views of China on the Eve of the Opium War —by Analyzing the Palmerston Letter and the UK Parliamentary Debates - YIHENG, MO (International Journal of Psychosocial Rehabilitation, 2020)
The first Opium War which took place in 1840 was the first large-scale war between China (Qing dynasty) and the western colonial power. After the war, China began to integrate with the world system which was dominated by the western industrial civilization. This article tries to figure out how the British government officials view China and how did the views affect the emerge of the war. By analyzing the and the parliamentary debates, especially the one held on April.7th-9th 1840, the finding is that the views of China showed British ethnocentrically and hegemony mentality, which is motivated by imperialism.